Fractional-order set-point weighted controllers - Bingi, K. (Springer International Publishing, 2020)
In the first section of this chapter, a critical review of the PID controller and modified PID control strategies include set-point weighted PID, PI-PD, and fractional-order PID is presented. In the second section, the design of fractional-order set-point weighted PID (SWPI Î» D Î¼ ) controller will be discussed. Here, the control strategy will be developed for standard, industrial, parallel and ideal configurations of the controller. In the third section, the design of fractional-order PI-PD (PI Î» -PD Î¼ ) controller in two single-loop control configurations are presented. In both cases, the conversion of controller parameters between various control strategies is presented. The next succeeding sections of the chapter will present the case studies on real-time pH neutralization and pressure processes for the implementation and evaluation of designed fractional-order set-point weighted PID control strategies. Finally, the last section will summarize the chapter. Â© Springer Nature Switzerland AG 2020.